The Assessment of Accuracy of GPS-positioning in Geobotanic Researches (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
Basic causes of data errors which arise in navigation have written. The methodology of estimation and decrease of a random error is offered at definition of geographical coordinate during field researches with GPS-receiver use.
Keywords: GPS-positioning, measurement error, geographical coordinates, Ozi Explorer.